Translational evaluation of magnetized saline water combined with ciclopirox olamine and piroctone olamine against Malassezia species and scalp seborrheic dermatitis - Rivetti, Nicolò; Lista, Simone; García-Chico, Celia; Khoramipour, Kayvan; Santos-Lozano, Alejandro; Minoretti, Piercarlo (Narra J, 2026)
Yeasts of the Malassezia genus are implicated in numerous skin conditions, including seborrheic dermatitis, pityriasis versicolor, and folliculitis. While ciclopirox olamine (CPO) and piroctone olamine (OCT) are effective anti-Malassezia agents, the activity of magnetized water against pathogenic yeasts remains unclear. The aim of this study was to examine the in vitro efficacy of magnetized saline water (MSW), alone or combined with CPO plus OCT, against three Malassezia species (M. furfur, M. globosa, and M. restricta) using broth microdilution to determine minimal inhibitory concentrations (MICs). A proof-of-concept study evaluating a shampoo containing MSW 30% + CPO 0.5% + OCT 1.0% in 20 patients with scalp seborrheic dermatitis (SSD) was subsequently conducted. Participants applied the shampoo four times per week for 12 weeks; efficacy was assessed by changes in a validated 16-point SSD severity score. The triple combination demonstrated additive-to-synergistic activity, with MIC values of 3.91 mg/L across all three species, representing a 2.0- to 4.0-fold MIC reduction compared to CPO + OCT alone, and synergy (FIC=0.31) for M. furfur. The total SSD score decreased by 33.9% after 12 weeks (p<0.001), with improvements in pruritus (49.0%), erythema (54.3%), and scaling (24.2%); all p values remained significant after Bonferroni correction (α=0.0125). These findings support MSW as a vehicle to potentiate the anti-yeast activity of CPO and OCT while reducing the chemical load, potentially offering a novel strategy for Malassezia-associated skin disorders. The open-label, single-arm design limits causal attribution, and larger controlled trials are needed.